Malaysian limestone orchids status : diversity, threat and conservation. - Rusea, Go; Lim, M.Y.L.; Phoon, S.N.; Yong, W.S.Y.; Tang, C.H.; Khor, H.E.; Abdullah, Janna Ong; Abdullah, J. (Nationaal Herbarium Nederland, 2009)
To date, a total of 288 species from 96 genera were identified from the limestone areas in Perlis and Padawan-Bau, Sarawak, of which many of these are restricted to limestone habitat and either endemic to Perlis or to Sarawak. Knowledge and data obtained from the field observation over the past 8 years leads us to report that at least 15 species endemic to limestone has become rare in the wild in Perlis, Bau and Padawan Sarawak. This was mainly attributed by: i) lack of emphasis by the government on understanding and protecting biodiversity in this kind of habitat; ii) lack of scientists willing to do research in dangerous and disaster prone limestone habitat; and iii) lack of knowledge and awareness among local communities on the importance of conserving and utilizing their natural resources in a sustainable manner.